2009
DOI: 10.5194/angeo-27-3421-2009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of variations in the ground magnetic field during substorms at mid latitudes

Abstract: Abstract. Substorms are known to cause geomagnetically induced currents (GIC) in power transmission lines through variations in the ground magnetic field. An improved knowledge and understanding of how the different phases of substorms affect the ground magnetic field will ultimately help to better understand how GIC arise. Although usually associated with high latitude power transmission networks, GIC potentially pose a risk to mid latitude networks such as the UK's National Grid. Using a list of substorm exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Comparing large R occurrence between the expansion and recovery phases, we find that large R is around 50% more likely in the expansion phase (Figure ) but overall about 50% more numerous during the recovery phase (Figure ) because over twice the time is spent in the recovery phase. This is consistent with the analyses of Turnbull et al () and Viljanen et al () who showed that the maximum ∂ H / ∂t within an interval from just before substorm onset to 60–90 min afterward preferentially occurs within about 10 min after onset (during the expansion phase) but can occur at any time within the 60‐90 min after substorm onset (which would include both the expansion and the longer recovery phase). Importantly, we have now extended their studies to compare this postonset occurrence to that at other times.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing large R occurrence between the expansion and recovery phases, we find that large R is around 50% more likely in the expansion phase (Figure ) but overall about 50% more numerous during the recovery phase (Figure ) because over twice the time is spent in the recovery phase. This is consistent with the analyses of Turnbull et al () and Viljanen et al () who showed that the maximum ∂ H / ∂t within an interval from just before substorm onset to 60–90 min afterward preferentially occurs within about 10 min after onset (during the expansion phase) but can occur at any time within the 60‐90 min after substorm onset (which would include both the expansion and the longer recovery phase). Importantly, we have now extended their studies to compare this postonset occurrence to that at other times.…”
Section: Discussionsupporting
confidence: 91%
“…The DP1 EOF and three other EOFs describing DP1 evolution can contribute about a fifth of the total variance (Shore et al, 2017). Third, the time of the maximum ∂H/∂t observed between 20 min before substorm onset to 60-90 min afterward peaks within a few minutes after the onset (Turnbull et al, 2009;Viljanen et al, 2006). However, ∂H/∂t can also be caused by other current sources, and these may be more predictable.…”
Section: Introductionmentioning
confidence: 99%
“…Another study restricted to 833 selected substorms in 1997 and 1999, before a solar maximum, showed a similar behaviour (Viljanen et al, 2006). Turnbull et al (2009) performed a corresponding investigation for 553 substorms at mid latitudes in 2000-2003 just after a solar maximum. They also found that large dH /dt are generally connected to westward ionospheric currents, but are also affected by smallerscale ionospheric structures.…”
Section: Introductionmentioning
confidence: 99%
“…These rapid fluctuations in the ground magnetic field are also the source of induced electric fields in the earth's surface. 1 Disruptions in sensitive technological systems resulting from geomagnetic-induced currents are mostly reported in higher geomagnetic latitude regions, but geomagnetically induced currents (GICs) large enough to cause transformer failures in power systems have been observed in mid and low latitudes as reported by Gaunt and Coetzee 2 . Ground magnetic observations have contributed immensely to the monitoring of the levels of geomagnetic activity and in studying the impact of geomagnetic storms on earth.…”
Section: Introductionmentioning
confidence: 99%